2019
DOI: 10.1111/dme.13912
|View full text |Cite
|
Sign up to set email alerts
|

Association between HbA1c and the development of cystic fibrosis‐related diabetes

Abstract: Aims To examine HbA 1c as a predictor of risk for future development of cystic fibrosis-related diabetes and to assess the association with the development of retinopathy in people with cystic fibrosis-related diabetes.Methods A 7-year retrospective longitudinal study was conducted in 50 adults with cystic fibrosis, comparing oral glucose tolerance test results with HbA 1c values in predicting the development of cystic fibrosis-related diabetes. Retinal screening data were also compared with HbA 1c measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In a study of 50 adults with cystic fibrosis, however, Choudhury et al . show that HbA 1c had a higher area under the receiver‐operating characteristic curve for predicting diabetes than fasting glucose, thus HbA 1c discriminated better. The authors propose using HbA 1c ≥ 37 mmol/mol (5.5%) to predict future prediabetes and cystic fibrosis‐related diabetes (CFRD).…”
mentioning
confidence: 93%
“…In a study of 50 adults with cystic fibrosis, however, Choudhury et al . show that HbA 1c had a higher area under the receiver‐operating characteristic curve for predicting diabetes than fasting glucose, thus HbA 1c discriminated better. The authors propose using HbA 1c ≥ 37 mmol/mol (5.5%) to predict future prediabetes and cystic fibrosis‐related diabetes (CFRD).…”
mentioning
confidence: 93%
“…According to the ISPAD guidelines ( 5 ), the following two diagnostic categories of CFRD have been established for patients screened with oral glucose tolerance test (OGTT) during periods of stable CF clinical conditions, based on fasting and 2-h glucose values: CFRD without fasting hyperglycemia (CFRD-FH - ) and CFRD with fasting hyperglycemia (CFRD-FH + ) ( Table 11 ). In addition, in symptomatic patients, the CFRD can be diagnosed if random blood glucose level is ≥200 mg/dL (≥11.1 mmol/L) on 2 or more occasions, and if HbA1c is ≥ 48 mmol/mol (6.5%) (48 mmol/mol), even though diagnosis of diabetes can also be made in CF patients that show HbA1c value below this range ( 45 ). During flare-up phases of the disease, when intravenous antibiotic therapy and/or systemic corticosteroid therapy is required, the diagnosis of CFRD can be made if a fasting glycemia ≥126 mg/dL (≥7 mmol/L) or a post-prandial blood glucose ≥200 mg/dL (≥11.1 mmol/L) is present for 48 h.…”
Section: Resultsmentioning
confidence: 99%
“…In their cohort, 36% of patients did not attend for their retinal screening appointment in the year assessed, but of those who did, 42% had evidence of retinopathy, ranging from mild to proliferative, and associated with maculopathy. 17 Choudhury et al 25 performed a retrospective seven-year longitudinal study in this same Welsh cohort and demonstrated that 44% of screened people with CFRD had retinopathy. 25 Yung et al 26 found retinopathy in 16% and 23% of a small cohort of patients at 5 years and 10 years of CFRD respectively, but HbA1c was not significantly different between people with and without retinopathy.…”
Section: Discussionmentioning
confidence: 99%